2023
DOI: 10.3390/su15064739
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility of Financial Cooperatives: A Multi-Level Analysis

Abstract: Cooperatives, which have a dual mission that includes both business and social goals, are of particular interest for the study of corporate social responsibility (CSR). The aim of this study was to examine how cooperative directors influence the CSR strategies of their organization. We used a multi-level conceptual framework, consisting of micro, meso, and macro levels, to analyze qualitative data (20 interviews, observation of two board meetings and analysis of over 25 public documents) collected through a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(242 reference statements)
0
2
0
Order By: Relevance
“…Some studies have reported that CSR activities can have a direct positive effect on consumer behavior (Quezado et al, 2022;Kumar and Srivastava, 2022;Sama et al, 2020). Other commentaries found that the effect of espoused CSR values on consumer behavioral and perceptual patterns is limited (Wagler, 2009;Adams, 2019;Villadsen and Lundberg, 2023) and can forge new policies and practices, which trigger more nuanced approaches to the uptake of CSR (Ijabadeniyi, 2020;Andersen and Høvring, 2020). This study uses the social realist lens to deepen understanding of the complex relationship between CSR and CR.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have reported that CSR activities can have a direct positive effect on consumer behavior (Quezado et al, 2022;Kumar and Srivastava, 2022;Sama et al, 2020). Other commentaries found that the effect of espoused CSR values on consumer behavioral and perceptual patterns is limited (Wagler, 2009;Adams, 2019;Villadsen and Lundberg, 2023) and can forge new policies and practices, which trigger more nuanced approaches to the uptake of CSR (Ijabadeniyi, 2020;Andersen and Høvring, 2020). This study uses the social realist lens to deepen understanding of the complex relationship between CSR and CR.…”
Section: Introductionmentioning
confidence: 97%
“…This phenomenon has made the reputation for CSR fashionable and a nice item to display on the business agenda and corporate communication strategies. The prevalence of the tactical and strategic use of CSR and sustainability-related terms in corporate communications is shifting accountability away from morality in business decision-making (Villadsen and Lundberg, 2023). This phenomenon is also perpetuating the post-crisis ethical order (Leins, 2020).…”
Section: Introductionmentioning
confidence: 99%